Variation of cerebrospinal fluid in specific regions regulates focality in transcranial direct current stimulation - Kashyap, Rajan; Bhattacharjee, Sagarika; Bharath, Rose Dawn; Venkatasubramanian, Ganesan; Udupa, Kaviraja; Bashir, Shahid; Oishi, Kenichi; Desmond, John E.; Chen, S. H. Annabel; Guan, Cuntai (Frontiers in Human Neuroscience, 2022)
Background: Transcranial direct current stimulation (tDCS) aims to focalize the current reaching the target region-of-interest (ROI). The focality can be quantified by dose-target-determination-index (DTDI). Despite having a uniform tDCS setup, some individuals receive focal stimulation (high DTDI) while others show reduced focality (‘non-focal’). The volume of cerebrospinal fluid (CSF), grey matter (GM), and white matter (WM) underlying each ROI govern the tDCS current distribution, thereby regulating focality. Aim: To determine the regional-volume parameters that differentiate the focal and non-focal group. Method: T1-weighted brain images from 300 age-sex matched adults were divided into three equal groups- (a) Young (20 ≥ x ˂ 40 years), (b) Middle (40 ≥ x ˂ 60 years), and (c) Old (60 ≥ x ˂ 80 years). For each group, inter and intra-hemispheric montages with electrodes at (1) F3 and right supraorbital region (F3-RSO), and (2) CP5 and CZ (CP5-CZ) were simulated, targeting the left- Dorsolateral Prefrontal Cortex and -Inferior Parietal Lobule, respectively. Both montages were simulated for two current doses (1 and 2mA). For each individual head simulated for a tDCS configuration (montage and dose), the current density at each ROI and their DTDI were calculated. The individuals were categorized into two groups- (1) Focal (DTDI ≥ 0.75), and (2) Non-focal (DTDI ˂ 0.75). The regional-volume of CSF, GM, and WM of all the ROIs was determined. For each tDCS configuration and ROI, three 3-way analysis of variance was performed considering- (i) GM, (ii) WM, and (iii) CSF as the dependent variable. The age-group, sex, and focality-group were the between-subject factors. Result: Regional CSF was the principal determinant of focality. For interhemispheric F3-RSO montage, a significant interaction-effect of age and focality was observed at Left Caudate Nucleus with the focal group exhibiting higher CSF volume. For intrahemispheric CP5-CZ montage, a significant-main effect was observed at the left pre- and post-central gyrus with the focal group showing lower CSF volume. Conclusion: The CSF channels the flow of tDCS current between electrodes with focal ROIs acting like reservoirs of current. The position of focal ROI in the channel determines the stimulation intensity at the target ROI.